SYMBOLIC ENACTMENTS AND RITUALIZED CONSTRUCTIONS OF THE ENVIRONMENT AMONG PENTECOSTAL CHRISTIANS IN SOUTH AFRICA - OJong, Vivian Besem (Journal of Dharma, 2011)
This research paper is about the relationship between religious belief, actions and attitudes of Pentecostal Christians towards the environment. Ethnographically positioned, it captures the ritualized and symbolic cognitive beliefs and practices of Pentecostal Christians in South Africa as well as the associated discourses. The paper also offers a discussion of the need to properly understand religion and shifting from text to territory. This requires methodological change of not just studying religion as written text but repositioning ourselves by studying it as a lived phenomenon to be studied through ethnographic accounts. It further explores some resilient Pentecostal belief patterns by showing how the environment is increasingly being seen in ritual terms.